W. MAAS, J. VAN RIJS, N. DE VRIES (eds.) - MVRDV. Costa Ibérica: Upbeat to the Leisure City - Fernández-Morales, Angélica (ZARCH, 2019)
Winy Maas, Jacon van Rijs, Natalie de Vries (eds.) MVRDV. Costa Ibérica: Upbeat to the Leisure City Barcelona: Actar, 2005. 321 págs. Idioma: inglés. ISBN: 978-8495273192